Urgency of Resilience and Optimism in Improving Students’ Mental Health - Mangestuti, Retno; Sholichatun, Yulia; Aziz, Rahmat; Wahyuni, Esa Nur (Jurnal Kajian Bimbingan dan Konseling, 2020)
Mental health study has become an intriguing and vital carried out by various experts according to their scientific discipline. This study aims to test the role of optimism as a mediator for the relationship of resilience with students’ mental health. The subjects were 320 students in four state Islamic colleges in East Java, Indonesia. Data obtained through the mental health scale, resilience scale, and optimism scale. Data were analyzed using regression analysis techniques. The analysis shows that the resilience has direct effects of 1.398 (p bigger than 0.01) and indirect effects of 0.312 (p bigger than 0.01) through optimism on students’ mental health. The implication of this result is the importance of resilience and optimism aspects to be considered in developing students’ mental health. Resilience will be more effective if the individual has a high level of optimism. Thus, to develop students’ mental health, these two abilities needed to be accelerated.